2001
DOI: 10.1007/s003300000699
|View full text |Cite
|
Sign up to set email alerts
|

Carboxymethyldextran-A2-Gd-DOTA enhancement patterns in the abdomen and pelvis in an animal model

Abstract: The aim of this study was to assess MR signal enhancement patterns of carboxymethyldextran (CMD)-A2-Gd-DOTA, a new macromolecular contrast agent, in the abdomen and pelvis of New Zealand white rabbits. Nine New Zealand white rabbits underwent MRI before and following injection of 0.05 mmol/kg body weight (bw) CMD-A2-Gd-DOTA (52.1 kDa), using turbo FLASH-, dynamic FLASH 60 degrees-, T1- and T2-weighted spin-echo and turbo spin-echo sequences up to 10 days p.i. Changes in blood and tissue signal intensities (del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…CMD-A2-Gd-DOTA was well tolerated in all anesthetized rats. This observation is in agreement with previous studies [15,34,39] that showed no toxic effects at a dose of 0.05 mmol. The hypothesis of the present study was that CMD-A2-Gd-DOTA can be used for characterization of tumor microvessels.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…CMD-A2-Gd-DOTA was well tolerated in all anesthetized rats. This observation is in agreement with previous studies [15,34,39] that showed no toxic effects at a dose of 0.05 mmol. The hypothesis of the present study was that CMD-A2-Gd-DOTA can be used for characterization of tumor microvessels.…”
Section: Discussionsupporting
confidence: 94%
“…Another potential clinical application is MR angiography [36][37][38]. Following its intravenous administration at a dose of 0.05 mmol Gd/kg body weight in an experimental rabbit model CMD-A2-Gd-DOTA demonstrated significant signal enhancement of abdominal organs and pelvic bone marrow, partial storage in the liver, and return to baseline signal intensities after 10 days postinjection [39]. To our knowledge, CMD-A2-Gd-DOTA has not been previously tested for its potential to characterize tumor microvessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our imaging test can track the location, estimate the quantity and provide information about the phagocytic activity of bone marrow cells. For example, we previously noted that normal bone marrow cells of young patients take up more iron compared to bone marrow cells of older patients (42,43). Our imaging test cannot determine the efficacy of the transplanted cells to regenerate bone.…”
Section: Discussionmentioning
confidence: 99%
“…Whole body MR has been used for screening patients with cancer predisposition syndromes, cancer staging of patients with hereditary increased radiosensitivity, staging of benign disease such as Langerhans Cell Histiocytosis, staging of non 18 F-FDG-avid tumors and patients without access to an 18 F-FDG PET/CT scan [40, 39, 41]. Since most tumors have a higher cell density than normal organs, the diffusional motion of water protons is more restricted in tumors and displayed by an increased signal intensity on diffusion weighted MR images [8, 42, 43].…”
Section: Integrate Information About Tumor Cell Density and Glucosmentioning
confidence: 99%